Agrarian questions, digitalisation of the countryside, immigrant labour in agriculture and the official discourses on rural development in the Uppsala region, Sweden - Cristián Alarcón (Italian Review of Agricultural Economics (REA), 2021)
This paper focuses on the Uppsala region of Sweden to analyse the dynamics of new agrarian questions intersecting with the prospects for immigrants to work in agriculture in the region. The paper seeks to explore the role of labour skills, agricultural automation and digitalisation of rural areas in local patterns of agrarian change and why and how they became barriers for the integration of immigrants through agricultural jobs in the region. The paper starts by laying out some basic conceptual insights to explore the current potential of agriculture to provide employment and livelihood possibilities for immigrants in Sweden and within this context the paper addresses issues of digitalisation and current technological trends in farming and rural development. Empirically, the paper is based on semi-structured interviews conducted with local farmers, officials working on rural development and integration programmes at the Uppsala county administrative board level, officials working on rural development and environmental planning at one rural municipality of the Uppsala region, and members of rural advocacy networks working with both rural development and integration issues in Sweden. In addition, the paper includes the analysis of regional and national policy documents developing new regional and rural development plans. Furthermore, the paper analyses information published in one of the leading Swedish magazines of the Federation of Swedish Farmers which focuses on agricultural development and technology and the paper uses other secondary sources.
Keywords: F22; Q10; Q16; Q18; 330; agrarian question; agriculture; capitalism; digitalization; immigrant labour; rural development; Sweden; technology